2011
DOI: 10.4236/ns.2011.37076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectral characterization, catalytic andbiological studies of new Ru(II) carbonyl Schiff base complexes of active amines

Abstract: The synthesis and characterization of several hexa – coordinated Ru(II) complexes of the type [Ru(CO)(B)(L)] (B = PPh<sub>3</sub>/AsPh<sub>3</sub>/py/pip; L = di-basic tetradentate ligand derived from the condensation of isatin with diamines) were reported. IR, electronic, <sup>1</sup>H- NMR, <sup>31</sup>P-NMR of the complexes are discussed. An octahedral geometry has been tentatively proposed for all these complexes. The new complexes have been tested for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Out of these five alcohols cyclohexanol and 1-phenylethanol show higher product conversion ratio than others and least activity is observed for 2-butanol. The compounds reported in this article show comparable catalytic efficiency with reported catalysts for supporting oxidation of alcohols by NMO or peroxides such as Ruazophelato compounds [47] or Ru-Schiff bases [48].…”
Section: Catalytic Oxidationsupporting
confidence: 70%
“…Out of these five alcohols cyclohexanol and 1-phenylethanol show higher product conversion ratio than others and least activity is observed for 2-butanol. The compounds reported in this article show comparable catalytic efficiency with reported catalysts for supporting oxidation of alcohols by NMO or peroxides such as Ruazophelato compounds [47] or Ru-Schiff bases [48].…”
Section: Catalytic Oxidationsupporting
confidence: 70%
“…[RuCl(CO)(PPh 3 )(S κ RaaiNR / )](PF 6 ) ( 3 ) has better catalytic activity compared to [RuH(CO)(PPh 3 ) 2 (SRaaiNR′)](PF 6 ) ( 2 ) in the presence of NMO. The catalytic oxidation properties of ruthenium(II) carbonyl complexes containing bidentate NN, NO, OO, tridentate NNN, ONO, ONS and tetradentate NNNN, NNOO donor ligands have been much studied . Ru―NHC complexes were recently described as useful catalysts in the alcohol oxidation process .…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of weak absorption bands in all the metal complexes at the range of 592 -574 cm -1 can be attributed to the stretching vibration of Metal -Nitrogen (M -N) and also appearance of weak absorption bands at all the metal complexes at the range of 481-422cm -1 can be attributed to the stretching vibration of Metal-Oxygen (M-O) which is similar to what was obtained in the literatures (Deoghoria et al, 2004 Bagihalli andAvaji, 2008 and Shahabadi and Kashanian, 2010). The Molar conductance measurement in DMSO are in the range 7.5-10.1 ohm -1 cm 2 mol -1 (Table 3).These values are relatively low showed that the complexes are non electrolytes (Raju and Balasubramanian, 2011). The low values indicate that the compounds are neutral.…”
Section: Resultsmentioning
confidence: 95%